Pengaruh Penerapan Model Pembelajaran Guided Discovery Learning Menggunakan Pendekatan Scientific Terhadap Hasil Belajar Siswa - Marchio Yosua Gratia Mamesah; Meyke Paat; Helen Joan Lawalata (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
This research aims to determine the effect of the guided discovery learning model on student learning outcomes in class 12 using a scientific approach; in this research, the researcher used 2 learning methods, one of which is the conventional method; the researcher used 2 classes as samples, where each class was 15 students in each class, was coded as class A for the control class and class B for the experimental class. The research instrument used was a question in the form of a posttest.